Perancangan Galeri Seni Lukis Ivan Hariyanto Di Surabaya - Santoso, Vania (Intra, 2014)
Paintings become one of the most important thing for decoration element nowadays, besides wants and needs of people about paintings for decoration element which its purpose to make rooms becomes more beautiful is very high. Making design work on